Da’wah Tarbiyah of the Indonesian Muslim Students Islamic Union (KAMMI): Political Communication and Public Opinion Perspective - Sunaryanto, Sunaryanto; Bakti, Andi Faisal; Rizal, Sofyan (UIN Fatmawati Sukarno Bengkulu, 2022)
The purpose of the study was to analyze Da’wah Tarbiyah of the Indonesian Muslim Students Islamic Union (KAMMI) from the perspective of political communication and public opinion. The methodology used is qualitative with a literature study approach. Data was collected from various journals, books, and research results published online. Data analysis techniques use flowing techniques (data reduction, data display, and drawing research conclusions). The nature of data analysis carried out in the study is descriptive-analytical by making descriptions and analyzing all library data that has been obtained. This study concludes that the Da’wah Tarbiyah of KAMMI has a romantic relationship with Prosperous Justice Party (PKS) and the Muslim Brotherhood. The typology of the Da’wah Tarbiyah is conservative, accommodating, and reformist, carrying out the vision of uniting the state with Islam. KAMMI built Da’wah Tarbiyah by conducting political communication with the PKS as the house of the movement. This organization makes public opinion so that the Muslim community accepts Da’wah Tarbiyah. This extra-campus organization fights political communication and public opinion by integrating da’wah and politics so that Islam can become a formal ideology in building the country.